Compartment Syndrome in Association with Tibial Plateau Fracture: Standardized Protocols Ensure Optimal Outcomes - Schwartz, Luke; Parola, Rown; Ganta, Abhishek; Konda, Sanjit; Rivero, Steven; Egol, Kenneth A. (The Journal of Knee Surgery, 2024)
The purpose of this study was to report on the treatment, results, and longer-term outcomes of patients who sustained a tibial plateau fracture with an associated leg compartment syndrome (CS). A total of 766 patients who sustained 766 tibial plateau fractures met inclusion criteria. Fourteen patients (1.8%) were diagnosed with CS in association with a tibial plateau fracture during their initial hospitalization, 13 at the time of presentation and 1 delayed. The treatment protocol consisted of initial external fixation and fasciotomy, followed by irrigation and debridement, and eventual closure. Fasciotomy cases included 2/14 (14.3%) single incision approaches and 12/14 (85.7%) dual incision approaches. Operative treatment of the tibial plateau fracture was performed at the time of final closure or once soft tissues were permitted. One case of CS that developed following definitive fixation was treated with fasciotomy and delayed primary closure after initial stabilization. Ten (71.4%) were available at 1-year follow-up. We compared these 10 cases to the patients with operative tibial plateau fractures without CS to assess for surgical, radiographic, clinical, and functional outcomes. We used a propensity match based on age, body mass index, sex, Charleson comorbidity index, and fracture type to reduce the presence of confounding biases. Standard statistical methods were employed. Those in the CS cohort were younger males (p < 0.05). At latest follow-up, function did not differ between those in the CS group compared with the non-CS cohort (p > 0.05). Clinically, knee flexion (130.7 vs. 126; p = 0.548), residual depression (0.5 vs. 0.2; p = 0.365), knee alignment (87.7 vs. 88.3; p = 0.470), and visual analog scale pain scores (3.0 vs. 2.4; p = 0.763) did not differ between the cohorts. Although infection was higher in the CS cohort, the overall complication rates did not differ between the CS patients and non-CS cohort (p > 0.05). Early identification and standardized treatment protocols for the management of CS that develops in association with a tibial plateau fracture lead to outcome scores that were not significantly different from patients who did not develop CS.
Keywords: tibial plateau; compartment syndrome; orthopaedic trauma